Factor VIIa interaction with endothelial cells and endothelial cell protein C receptor - Pendurthi, Usha R (2010)
Plasma coagulation factor VIIa (FVIIa) initiates the coagulation cascade by binding to its cofactor, tissue factor (TF) on cell surfaces, which eventually leads to fibrin deposition and platelet activation. Recent studies showed that FVIIa also binds to endothelial cell protein C receptor (EPCR), a known cellular receptor for anticoagulant protein C\activated protein C, on the endothelium. The present article reviews our current knowledge of FVIIa interaction with EPCR and discusses the potential significance of this interaction in hemostasis, treatment of bleeding disorders with pharmacological doses of FVIIa and FVIIa clearance.